Reconstructing the Concept of Women in Islamic and Pesantren Educational Perspectives - Muslih, Mohammad; Syarifah, Syarifah; Ahmadan, Madani (Jurnal Penelitian Pendidikan, 2025)
The idea of women in Islam is examined in this article as a key topic in modern Islamic studies, covering theological, sociological, and pedagogical facets. By examining the viewpoints of the Qur'an, Hadith, Islamic academic tradition, and historical precedents, this study seeks to provide a comprehensive picture of women's strategic position and role. This article illustrates how Islam sees women as spiritually equal beings with a variety of roles through scriptural and contextual study. The Qur'an and Hadith's endorsement of men and women's spiritual equality, which dispels patriarchal prejudices, opens the topic. The article then examines the ideas of "Sayyidah" and "Umm," which show how women's roles in the home and in society are balanced. Exemplary characters like Khadijah, Aisha, and Fatimah are also presented in the analysis as models of perfect women who achieve achievement in their careers, education, and spiritual lives. It is also stressed that women play a crucial role in forming the character of future generations as "madrasah al-ūlā" (first school). To sum up, Islam views women as active and important participants in the advancement of civilization. In the context of women's education at establishments like the Gontor Putri Modern Islamic Boarding School, which seeks to create ideal Muslim women capable of serving as leaders and educators in society, these ideas are not merely theoretical but also applicable.